Keran Air Wudhu Otomatis Menggunakan Sensor Infrared Sebagai Upaya Meminimalisasi Pemborosan Air - M. Iman Wahyudi; Rifki Abdul Aziz (Journal of Applied Computer Science and Technology, 2022)
The use of water in taking ablution is not in accordance with the excessive, it is one indication of the waste of water in use, the water faucet will continue to be open and the water will continue flow maximally, and there are also happens people forget to close the water tap after ablution then it will result in undue water wastage. In this study the author tries to develop a water saving scheme using infrared sensor and an Arduino-based and also will try to calculate the percentage efficiency of water use in ablution. Based on the results of the test the writer obtain automatic water faucets are more effective to save the water than the manual water faucets, it can be concluded that the use of an automatic ablution water faucets can save water average 40,04%.